2001
DOI: 10.1128/cdli.8.6.1097-1103.2001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum and Cell-Specific Cytokines in Humans

Abstract: Cytokines function at the cellular, microenvironmental level, but human cytokine assessment is most commonly done at the macro level, by measuring serum cytokines. The relationships between serum and cellular cytokines, if there are any, are undefined. In a study of hospitalized patients in Malawi, we compared cytometrically assessed, cell-specific cytokine data to serum interleukin 2 (IL- ؊ T cells producing induced IL-8 (r s ‫؍‬ ؉0.40 and r s ‫؍‬ ؉0.56, respectively). Thus, the strength of associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 32 publications
5
61
2
1
Order By: Relevance
“…This is somewhat of an assumption in regard to both measures. We have previously shown that, in general, serum and cell-specific cytokines are at best only weakly associated with one another (13). Correlations between cell and serum cytokine parameters were not infrequently even negative, consistent with the hypothesis that serum and cell-specific cytokines measure different things (13).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is somewhat of an assumption in regard to both measures. We have previously shown that, in general, serum and cell-specific cytokines are at best only weakly associated with one another (13). Correlations between cell and serum cytokine parameters were not infrequently even negative, consistent with the hypothesis that serum and cell-specific cytokines measure different things (13).…”
Section: Discussionsupporting
confidence: 76%
“…We have previously shown that, in general, serum and cell-specific cytokines are at best only weakly associated with one another (13). Correlations between cell and serum cytokine parameters were not infrequently even negative, consistent with the hypothesis that serum and cell-specific cytokines measure different things (13). Interestingly, for the patients with spontaneous cytokine production discussed here, the correlations between serum and peripheral-blood cell-specific cytokines were all in a positive direction but, as with the more general population, generally with only weak correlation coefficients (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many research studies involving serum and plasma cytokine assessments, this approach does have a number of limitations. Serum and plasma cytokine levels can be affected by receptor binding, temperature degradation, urinary excretion, and cytokine breakdown within reacting cells (15). To be more precise, the present study demonstrated the role of some inflammatory (i.e., IFNγ, IL-12p40, IL-6 and TNFα) and anti-inflammatory (i.e., IL-4 and IL-10) cytokines mRNA extracted from liver and spleen tissues, as they are considered to be the most affected organs.…”
Section: Production Of Cytokines Detected By Rt-pcrmentioning
confidence: 99%
“…Blood cytokines are produced not only by those cell types considered to play pivotal roles in the immune system as well as in inflammatory responses, including lymphocytes, monocytes, and mast cells, but also by macrophages and, for some cytokines, also fibroblasts, neutrophils, and endothelial cells (26). So, it should be NOTE: ORs estimated by CLR models for tertiles of plasma cytokine concentrations (tertile cut points based on the distribution of cytokine levels for control subjects).…”
Section: Mori Et Al (25) Studied Cd4mentioning
confidence: 99%